PENDIDIKAN KEWARGANEGARAAN DAN WAWASAN KEBANGSAAN MENUJU VISI INDONESIA 2025 - Rusnaini, Rusnaini (Jurnal Inovasi Pendidikan, 2010)
This paper discusses about developing characteristics of being a citizen. The aim of this paper is to develop personality of citizens who are fully participating, competent, responsible, and having commitment to the values and objectives of the state in accordance with the vision of Indonesia in 2025. This can be done by developing a national perspective, which is fostering a sense of nationality through the study of civics education learning, the actualization of nationality through civics curriculum changes, and actualization of national spirit through the development of civics education materials.